2016
DOI: 10.3109/03014460.2015.1119309
|View full text |Cite
|
Sign up to set email alerts
|

Association of heat shock protein70-2 (HSP70-2) gene polymorphism with obesity

Abstract: Background: Obesity is a major risk factor of chronic-diseases, including cardiovascular-diseases (CVD). Increasing evidence is showing the association of heat-shock protein (HSP) with type-2 diabetes and CVD; however, there is little data on the relationship between the geneticpolymorphisms of HSP70-2 with obesity. Aim: The present study has investigated the association between 1267HSP70-2 genetic polymorphism and obesity in an Iranian population with 317 subjects. Subjects and methods: Anthropometric paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The results of other studies have suggested that the HSP70.2 (heat shock 70 kDa protein 1B) gene might be a candidate gene involved in obesity and type 2 diabetes 38 , 39 . As well as being involved in the immune system and cellular response, these genes are involved in ATP binding, ATPase activity and ATP metabolic processes, which provide the direct energy source for the body.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies have suggested that the HSP70.2 (heat shock 70 kDa protein 1B) gene might be a candidate gene involved in obesity and type 2 diabetes 38 , 39 . As well as being involved in the immune system and cellular response, these genes are involved in ATP binding, ATPase activity and ATP metabolic processes, which provide the direct energy source for the body.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological factors, including white blood cell (WBC), red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), platelet count (PLT), platelet distribution width (PDW) were measured in all the subjects, as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is essential to identify more genetic markers that can predict individual NIHL susceptibility potentially. The abnormity of HSP70 have been demonstrated to be related to many diseases, such as obesity [ 19 ], congenital sideroblastic anemia [ 20 ], coronary artery disease [ 21 ] and age-related cataract [ 22 ]. In the research field of NIHL, two studies both suggested an important role of HSP70 in the resistance to NIHL [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%